2023
DOI: 10.1186/s13613-023-01136-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of clinical phenotypes in decisions to limit life-sustaining treatment for very old patients in the ICU

Abstract: Background Limiting life-sustaining treatment (LST) in the intensive care unit (ICU) by withholding or withdrawing interventional therapies is considered appropriate if there is no expectation of beneficial outcome. Prognostication for very old patients is challenging due to the substantial biological and functional heterogeneity in that group. We have previously identified seven phenotypes in that cohort with distinct patterns of acute and geriatric characteristics. This study investigates the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…While the restricted use of these aggressive therapies in geriatric patients reflects the careful clinical judgment of the potential risks and benefits, specific studies linking age to limited COVID-19 therapies are scarce [ 19 , 20 ]. Previous studies have shown that an advanced age is often associated with decisions to limit life-sustaining treatment [ 21 , 22 ], suggesting that similar considerations may influence less aggressive treatment approaches for geriatric patients with COVID-19. These associations underscore the need for nuanced clinical decision making that takes into account the unique complexities of treating critical illness in the older population.…”
Section: Discussionmentioning
confidence: 99%
“…While the restricted use of these aggressive therapies in geriatric patients reflects the careful clinical judgment of the potential risks and benefits, specific studies linking age to limited COVID-19 therapies are scarce [ 19 , 20 ]. Previous studies have shown that an advanced age is often associated with decisions to limit life-sustaining treatment [ 21 , 22 ], suggesting that similar considerations may influence less aggressive treatment approaches for geriatric patients with COVID-19. These associations underscore the need for nuanced clinical decision making that takes into account the unique complexities of treating critical illness in the older population.…”
Section: Discussionmentioning
confidence: 99%
“…An assessment of the CFS by two different specialists when possible (for example, a geriatrician and an intensivist) is advisable, especially when the CFS is used as a triage tool among others. The identification of phenotypes with specific geriatric and acute characteristics, found to be associated with ICU mortality, may help move past an evaluation based only on the CFS [ 74 ].…”
Section: Use Of Scales In Emergency Situations For Critically Ill Old...mentioning
confidence: 99%
“…Decisions to limit life-sustaining treatment (LST) should account for baseline status, quality of life, survival potential, functional outcomes, and treatment burden. Mousai et al [ 140 ] illustrate that integrating clinical phenotypes with cultural factors and information about critical care course enhances predictive discrimination accuracy for LST in very old ICU patients. Clinicians can make these decisions either before ICU admission or as the patient’s condition evolves.…”
Section: Introductionmentioning
confidence: 99%